COMBINATION OF POLYTHYLENE TEREFTALAT NESTING AND PRONE POSITION AT THE STANDARD BOX CARE TO THE VITAL SIGNS AND LENGTH OF STAY ON THE LOW BIRTH WEIGHT BABIES - Deviana, Meli; Pramono, Noor; Suwondo, Ari (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2020)
Background: The use of nesting and position prone facilitates Low Birth Weight Babies by conditioning it as in the mother's womb which aims to facilitate Low Birth Weight Babies in the development of physiological functions and achieve physiological function stability.Aims: This study aims to explain the effectiveness of design nesting with material polyethylene terephthalate and the position of prone with standard care using a box of baby warmers for the length of stay which is observed from the achievement of the stability of vital signs on LBW.Methods: This is a Quasi-Experimental Design study with non-equivalent control group design. The study population was all LBW treated in the Perinatal room with a sample of 36 LBW and consecutive sampling. This research was conducted in the Perinatal Room at RSUD RAA Soewondo Pati and RSUD Dr. R. Soetrasno Rembang. Statistical test for paired groups using Wilcoxon and for unpaired groups using Kruskall Wallis.Results: The combination of nesting polyethylene group with position prone achieved faster vital signs stability and shorter duration of treatment compared to the control group with p = 0.001 for temperature, respiration and oxygen saturation.Conclusions: The combination of polyethylene terftalat nesting and prone position is effective to reduce the duration of treatment duration, and may achieve the stability of vital signs of low birth weight infants. This intervention can be used as LBW care during hospital and home care. Keywords: Nesting, Position Prone, Polyethylene Tread, Length of Stay, Baby Vital Signs.